Research on Status of Water Use and Quality of Domestic Supply Water in Trang Bang District, Tay Ninh Province - Tri Quang Hung, Nguyen; Minh Ky, Nguyen; Hung Danh, Dinh; Phuong Vu, Thai; Ngoc Anh Tuan, Huynh (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 4DO - 10.25073/2588-1094/vnuees.4251, 2018)
Abstract: This paper presents the results of status of water use and quality of domestic water supplies in Trang Bang district, Tay Ninh province. Ratio of the local population could be accessed the safe drinking water in Trang Bang district which recording of low frequency. The study was conducted the sampling and evaluation of water quality in nine rural water supply stations in Phuoc Chi, Binh Thanh and Phuoc Luu communes, Trang Bang district. Analyzing results of the important water quality parameters at the rural water supply stations in Trang Bang district showed that these parameters met requirements National Technical Regulation on domestic water quality QCVN 02:2009/BYT and drinking water quality QCVN 01:2009/BYT. However, some monitoring samples ofE.coli level did not meet the water supply requirements for domestic and drinking purposes. Correlation coefficients among water quality parameters illustrated the strongly relationships at statistically significant (p<0.05). Results of PCA showed three principal components (PCs) with obtainable eigen values was equal to 1.287 and total cumulative variance within 86.426%. It means the studying results could be used to assessing and interpreting of domestic supply water quality status in Trang bang district, Tay Ninh province. Keywords: Water quality, Trang Bang, domestic, drinking water, water supply. References [1] Khan, N., Syed T.H., Javid H., Nargis J., Shabir A., Riaz U., Zain U., Abdus S., (2012). Physiochemical evaluation of the drinking water sources from district Kohat, Khyber Pukhtunkhwa, Pakistan. International Journal of Water Resources and Environmental Engineering, 4(10):302-313. [2] World Health Organization (2011). Guidelines for Drinking-Water Quality, 4th Edition.World Health Organization, Geneva. [3] Bruning-Fann C.S., Kaneene J.B., (1993). The effects of nitrate, nitrite and N-nitroso compounds on human health. Vet Hum Toxicol, 35:521-538. [4] Cantor K.P., (1997). Drinking water and cancer. Cancer Causes Control, 8:292-308. [5] Jing Z., (2012). The impact of water quality on health: Evidence from the drinking water infrastructure program in rural China. Journal of Health Economics, 31(1):122-134. [6] Ying Z., Xuemei H., Zhiguang N., (2018). Health risk assessment of haloacetonitriles in drinking water based on internal dose. Environmental Pollution, 236:899-906. [7] Gleick, P.H. (Ed.). (1993). Water in Crisis: A Guide to the World’s Fresh Water Resources. Oxford University Press, New York. [8] WHO-UNICEF (2015). Progress on Sanitation and Drinking Water: 2015 Update and MDG Assessment. UNICEF Publisher, New York, US. [9] Bartram, J., Cairncross, S., (2010). Hygiene, Sanitation, and Water: Forgotten Foundations of Health. PLoS Medicine, 7(11):e1000367. [10] Cục thống kê tỉnh Tây Ninh (2017). Niên giám thống kê tỉnh Tây Ninh năm 2016. Tây Ninh. [11] Boyacioglu H., (2006). Surface water quality assessment using factor analysis. Water SA, 32(3):389–393. [12] Jolanta J., Elzbieta R., Katarzyna R., (2017). Principal Component Analysis And Cluster Analysis In Multivariate Assessment Of Water Quality. J. Ecol. Eng, 18(2):92–96. [13] Lianne M., Lalita B., Tasha E., Cheryl L.W.. (2017). Use of Principal Components Analysis and Kriging to Predict Groundwater-Sourced Rural Drinking Water Quality in Saskatchewan. Int. J. Environ. Res. Public Health, 14(9):1065-1089. [14] Rwoo, M.A., H. Juahir, N.M. Roslan, A. Endut, M.K.A. Kamarudin, M.A. Amran., (2017). Assessment of drinking water quality using principal component analysis and partial least square discriminant analysis: A case study at water treatment plants, Selangor. J. Fundam. Appl. Sci., 9(2S):157-173. [15] Simeonov V., Stratis J.A., Samara C., Zachariadis G., Voutsa D., Anthemidis A., Sofoniou M., Kouimtzis T., (2003). Assessment of the surface water quality in Northern Greece. Water Research, 37(17):4119-4124. [16] Shyu, G.S., Cheng, B.Y., Chiang, C.T., Yao, P. H., Chang, T. K., (2011). Applying factor analysis combined withkriging and information entropy theory for mapping and evaluating the stability of groundwater quality variation in Taiwan. Int. J. Environ. Res. Public Health. 8:1084-1109. [17] Yang C.Y., Cheng M.F., Tsai S.S., Hsieh Y.L., (1998). Calcium, Magnesium, and Nitrate in Drinking Water and Gastric Cancer Mortality. Jpn J Cancer Res, 89:124-130. [18] EPA (2008).State of the Environment Report.Environmental Protection Agency, Wexford, Ireland. [19] Cheng L.J.Y., Oh K.S., Poh P.E., Chong M.N., (2017). Prospects of hybrid rainwater-greywater decentralised system for water recycling and reuse: A review. Journal of Cleaner Production, 142(4):3014-3027. [20] Sinha D.K., Rastogi G.K., Kumar R., Kumar N., (2009). Correlation study among water quality parameters an approach to water quality management. J Environ Sci Eng., 51(2):111-114. [21] American Water Works Association (1999). Water Quality and Treatment. McGraw-Hill, Inc., New York, USA. [22] World Health Organization (1996). Ammonia in Drinking-water: Guidelines for drinking-water quality (2nd Ed). Geneva, Switzerland. [23] Belkhiri, L., Boudoukha, A., Mouni, L., (2011). A multivariate statistical analysis of groundwater chemistry data. Int. J. Environ. Res., 5:537–544. [24] Chapagain, S.K., Pandey, V.P., Shrestha, S., Nakamura, T., Kazama, F., (2010). Assessment of deep groundwater quality in Kathmandu Valley using multivariate statistical techniques. Water. Air. Soil Pollut., 210:277–288. [25] Amadi, A.N., (2012). Quality Assessment of Aba River using heavy metal pollution index. American Journal of Environmental Enginerring, 2(1):45-49. [26] Kaiser, H.F., (1960). The application of electronic computers to factor analysis. Educ. Psychol. Meas., 20:141–151. [27] Osei J., Nyame F.K., Armah T.K., Osae S.K., Dampare S.B., Fianko J.R., Adomako D., Bentil N., (2012). Application of multivariate analysis for identification of pollution sources in the Densu Delta Wetland in the vicinity of a landfill site in Ghana. Journal of Water Resource and Protection, 2(12):1020-1029. [28] Alagumuthu G., and Rajan M., (2010). Chemometric studies of water quality parameters of Sankarankovil block of Tirunelveli, Tamilnadu. Journal of Environmental Biology, 31(5):581-586. [29] Mohammad A., Miri M., Ebrahimi A., Khorsandi H., Nemati S., (2016). Monitoring of THMs concentration in Isfahan water distribution system and zoning by GIS, a case study in the Centre of Iran. Iranian Journal of Health, Safety and Environment, 3(1):421-427. [30] Ky N.M., Lam N.H., (2014). Using multivariate statistical techniques to assess water quality of Nhu Y river in Thua Thien Hue province. Journal ofScience & Technology Development, 17(M1):50-60.